Reflections on having participated at the Pre-NORMA workshop - Sacheva, Shipra; Hvalsøe Schou, Marit; Lindenskov Tamborg, Andreas (NOMAD Nordic Studies in Mathematics Education, 2016)
As PhD students we experienced several advantages in participating in a workshop like pre-NORMA ...